Memperkuat Eksistensi Pendidikan Islam dalam Menghadapi Era Revolusi Industri 4.0 - Kharis Syuhud Mujahada (SALIHA: Jurnal Pendidikan & Agama Islam, 2019)
His paper seeks to provide solutions to Islamic education in the face of the Age of Industrial Revolution 4.0. As we know together, that era 4.0 has a broad impact on all lines of life, including in education. The era that gave birth to this disruption phenomenon demanded the world of Islamic education to participate in adjusting. Graduates of Islamic education are now faced with new challenges, demands, and needs that have never existed before. So it is necessary to update and innovate the system, governance, curriculum, human resource competencies, facilities and infrastructure, culture, work ethic, and others. If not, Islamic education will be increasingly left behind and obsolete. Therefore, it is necessary to look for concrete steps for Islamic education in order to be able to remain competitive in this disruption era. The solution step is to participate in discussing themselves. this is intended so that Islamic education is not left behind as well as a form of efforts to improve quality in Islamic education in the era of disruption.